Sultan Hamengku Buwono Ii: Pembela Tradisi dan Kekuasaan Jawa - Marihandono, Djoko (Makara Human Behavior Studies in Asia, 2008)
Since his younger age, Sultan Hamengku Buwono II indicated that he always refused the Dutch intervention in the sultanate’s palace of Yogyakarta. He became rival of the Dutch governments because of his opinion that the Dutch had intervented too much in the cultural and noble life’s sultanate of Yogyakarta. After his coronation as a sultan in Yogyakarta in 1792, he kept his mind to guard the Java’s glorious tradition and the traditional power of the Sultan. This condition caused a great conflict between the Sultan and the Dutch government. Sultan HB II tried to refuse all the intervention of Dutch Government. As consequences of his character, the colonial government proposed to replace the Sultan with the crownprince. During his life, he accepted twice decoronation (in 1811 by Gouvernor General Daendels and in 1812 by Leutnant General Raflles) and he was exiled three times (Penang in 1812, Ambon in 1817 and Surabaya in 1825). Finally, the Dutch Government recalled him to be a sultan in Yogyakarta to persuade all princes who supported Prince Diponegoro’s revolt. Unfortunately, till his death, he still refused to cooperate with the colonial government. To the present, there are many works of this sultan as: literary works, philosophy, arts dan physical buildings, which describes his characters toward the colonial government.